ISOTOPIC REGIME OF SUBGLACIAL LAKE VOSTOK ON EVIDENCE FROM DEEP ICE CORE STUDIES - A. Ekaykin A.; V. Lipenkov Ya.; A. Kozachek V.; А. Екайкин А.; В. Липенков Я.; А. Козачек В. (Ice and Snow, 2015)
On the 5th of February 2012 the long-lasting project of deep ice drilling at Russian Antarctic station of Vostok was completed by the penetration to the subglacial lake at the depth of 3769.3 m. The study of the ice core representing the frozen lake water and obtained as a result of the drilling, has allowed to make preliminary conclusions on the lake hydrological regime before its direct studies. In this work we present the new isotopic data (dD and d18O) from the 5G-2 ice core from the depth interval 3600–3720 m. The measurements were performed in the recently established Climate and Environment Research Laboratory of Arctic and Antarctic Research Institute (St. Petersburg,Russia). The comparison of the new isotope profile with the previously published 5G-1 data (3540–3650 m) demonstrates a good reproducibility, which means a satisfying quality of the measurements. The analysis of the whole available lake ice thickness isotope profile (3540–3720 m) has allowed to obtain a new information on theLakeVostok’s hydrological regime. Based on the isotopic behavior, the lake ice core is divided into three sections. The first (3540–3619 m) corresponds to the so-called «lake ice 1», the ice containing visible mineral inclusions that was formed close to the western lake shore. The isotopic variability in this section was formed due to the changing conditions and mechanisms of the ice formation (ice accretion rate, concentrations of the frazil ice crystals and frozen water pockets). The second (3619–3647 m) is characterized by a weak correlation between deuterium and oxygen 18, which is interpreted as an influence of the hydrothermal activity on the lake’s isotopic regime. In the third section (3647–3720 m), formed over the deep basin in the southern part of the lake, the isotopic variability is reduced due to the relatively stable steady-state conditions of the ice formation. At the same time, the signature of the lake water isotopic variability is observed here, which is attributed to the pulsations of the flux and/or ...